EMPOWERMENT OF PHARMACEUTICAL STAFF ON PHARMACEUTICAL SERVICES TO INCREASE PATIENT SATISFACTION - Irmayani Irmayani; Sri Melda Bangun; Raisha Octavariny; Nurjannah Syafitri; Luci Riani Br Ginting (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2022)
The quality of good and quality health services is marked by the provision of excellent, fast, precise and responsive service to customers which has an impact on customer satisfaction with the services provided. The hospital is one of several existing health service centers. There are many parts in the hospital, one of which is the pharmacy installation which is one of several parts in the hospital, which has an important role in addition to other parts. The PKM activity carried out at Grandmed Lubuk Pakam Hospital aims to provide assistance to pharmacy staff on pharmaceutical services to increase patient satisfaction. The methods used are discussion, lecture, simulation and empowerment. The implementation of PKM activities was carried out in March 2022. The participants in this activity were all 34 officers at the pharmacy installation. Evaluation of the activities that have been carried out using the instruments that have been prepared. From the PKM activities that have been carried out, it can be explained that there was an increase in participants' understanding of the material presented by the resource persons by 70.6%. The ability of participants to understand the material presented by the resource person will be an asset for officers in providing excellent service in hospitals, especially in pharmaceutical services which have an impact on patient satisfaction. It is expected that the activity participants are able to apply the strategy of providing excellent, fast, precise and responsive service so that patients feel satisfied with the services provided.